2014
DOI: 10.1093/abbs/gmu097
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 treatment ameliorates alcoholic fatty liver through activation of AMPK-SIRT1 pathway

Abstract: Fibroblast growth factor 21 (FGF21), a recently identified member of the FGF superfamily, is mainly secreted from the liver and adipose tissues and plays an important role in improving metabolic syndrome and homeostasis. The aim of this study is to evaluate the role of FGF21 in alcoholic fatty liver disease (AFLD) and to determine if it has a therapeutic effect on AFLD. In this paper, we tested the effect of FGF21 on alcohol-induced liver injury in a murine model of chronic ethanol gavage and alcohol-treated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 31 publications
(29 reference statements)
2
75
1
Order By: Relevance
“…Asrih et al found that FFA impairs FGF21 action in HepG2 cells [27]. In vivo , FGF21 enhances hepatic insulin sensitivity [19], ameliorates AFLD [30], and regulates the adaptive metabolic response of the liver to prolonged fasting [21]. However, whether and how FGF-21 directly stimulates hepatocytes on glucose uptake is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Asrih et al found that FFA impairs FGF21 action in HepG2 cells [27]. In vivo , FGF21 enhances hepatic insulin sensitivity [19], ameliorates AFLD [30], and regulates the adaptive metabolic response of the liver to prolonged fasting [21]. However, whether and how FGF-21 directly stimulates hepatocytes on glucose uptake is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among those molecules, AMPK appears to be the most important target of ethanol in liver. AMPK activity is impaired by ethanol exposure and then stimulates downstream effectors, for example, lipin 1 (39), resulting in subsequent inhibition of fatty acid ␤-oxidation and stimulation of lipogenesis that contribute to accumulation of TG in vitro or in vivo (7,40,41). Except for SIRT1 (3), FGF21 (fibroblast growth factor 21) (41), and adiponectin (7), very little is known about the molecular mechanisms leading to the impairment of AMPK activity under ethanol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It also increases energy expenditure, FFA oxidation, and mitochondrial function via activating the AMPK-SIRT1-PGC-1/ pathway and UCP1 [70], and counteracts ER stress [65]. On this basis, experimental FGF21 administration improved obesity, diabetes, and NASH [71], and ameliorated diabetic and obesity-related kidney injury in preclinical models of CKD through multiple mechanisms [72,73] (Table S2).…”
Section: The Liver As a Determinant Of Kidney Injurymentioning
confidence: 99%